The Kovacs guide to electronic library collection development : essential core subject collections, selection criteria, and guidelines - Kovacs, Diane K. (New York : Neal-Schuman Publishers, 2009)
The book is a guide to librarians in any kind of library to find a good stuff, march it to local needs, make it accessible, and develop processes to fold high quality electronic resources into their traditional workflow.
Includes bibliographical references and index.
uaj 07/05/13
Loans
Keywords: Digital libraries; Electronic library; Library collection development